SENTIMEN ANALISIS TERHADAP KEBIJAKAN PEMBELAJARAN JARAK JAUH SELAMA PANDEMI COVID-19 MENGGUNAKAN ALGORITMA NAÏVE BAYES - Darsono Nababan (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2021)
Social media is a means to convey aspirations directly, but every aspiration is from social media users. Everyone who expresses opinions on social media contains positive, negative, and neutral sentiments. The implementation of the Ministry of Education and Culture's policy on the implementation of distance learning policies during the pandemic COVID-19 received various responses from the people of Indonesia. neutral as many as 894 comments, then 52 comments with negative sentiment, and 32 comments with positive sentiment with an accuracy value of 98.79%